2017
DOI: 10.21037/atm.2017.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of Agrimonia pilosa Ledeb aqueous extracts on blood coagulation function

Abstract: Background: Agrimonia pilosa Ledeb (APL) has showed anticoagulant and antithrombotic activities in some studies, whereas its actual effects on blood coagulation are still unclear. This study was designed to observe the in vitro effects of APL aqueous extracts on blood coagulation, as well as to investigate the underlying mechanisms.Methods: Studies were divided into four groups: 0, 4, 20, and 80 g/L of APL aqueous extracts mixed with plasma or whole blood samples. Clotting time of whole blood, plasma coagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, the principal of TCM to treat cancer patients receiving chemotherapy is based on nourishing Yin fluid and enriching the blood. The Shen Cao granules included the following functions: Adenophora stricta, Dendrobium nobile , and Lycium chinense could nourish Yin and generate body fluid 22,23 ; Carapax Testudinis has the function of replenishing vital essence and marrow 24 ; Agrimonia pilosa , 25 Lithospermum erythrorhizon , 26 and Eclipta prostrata 27,28 could enrich blood and staunch bleeding (Supplemental Table 1). A combination of these herbs in appropriate proportions is expected to tonify the liver and kidney, nourish body fluid, and minimize noxious heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the principal of TCM to treat cancer patients receiving chemotherapy is based on nourishing Yin fluid and enriching the blood. The Shen Cao granules included the following functions: Adenophora stricta, Dendrobium nobile , and Lycium chinense could nourish Yin and generate body fluid 22,23 ; Carapax Testudinis has the function of replenishing vital essence and marrow 24 ; Agrimonia pilosa , 25 Lithospermum erythrorhizon , 26 and Eclipta prostrata 27,28 could enrich blood and staunch bleeding (Supplemental Table 1). A combination of these herbs in appropriate proportions is expected to tonify the liver and kidney, nourish body fluid, and minimize noxious heat.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs could worsen the deficiency of body fluid (Yin fluid) due to their noxious heat effects and the dysfunction of viscera during treatment. Patients undergoing chemotherapy often experience mouth sores, discomfort of the main 5 internal organs (heart, liver, spleen, lungs, and 22,23 ; Carapax Testudinis has the function of replenishing vital essence and marrow 24 ; Agrimonia pilosa, 25 Lithospermum erythrorhizon, 26 and Eclipta prostrata 27,28 could enrich blood and staunch bleeding (Supplemental Table 1). A combination of these herbs in appropriate proportions is expected to tonify the liver and kidney, nourish body fluid, and minimize noxious heat.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this herb contains various tannins, such as agrimoniin and ellagic acid, and flavonoids, such as apigenin-7- O -glucuronide (A7OG) and luteolin-7- O -glucuronide. This herb, which has a slightly bitter and astringent taste, has been traditionally used to treat hemostasis, intestinal disorders, and inflammation [ 3 , 4 ]. Recent studies have reported the herb as having anticancer, antioxidant, and anti-inflammatory properties [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…( A. pilosa ) has been traditionally used in Japan and China as an antidiarrheal, hemostatic, and antiparasitic agent [ 11 ]. Pharmacologically, A. pilosa exhibited anti-inflammatory activity in Porphyromonas gingivalis lipopolysaccharide-induced RAW 264.7 cells [ 12 ], antitumor activity in lung cancer, breast cancer, and prostate cancer cell lines through G0 cell cycle arrest [ 13 ], antiviral activity against SARS-CoV-2 [ 14 ], antioxidant effect through DPPH and superoxide radical scavenging activity [ 15 ], antibacterial activity against methicillin-resistant Staphylococcus aureus [ 16 ], osteogenic differentiation promotion in MC3T3-E1 cells by targeting miR-107 [ 17 ], blood coagulation function [ 18 ], and anti-hyperglycemic activity by inhibiting inflammatory response in high-fat diet-fed rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%